2022
DOI: 10.1371/journal.pone.0267583
|View full text |Cite
|
Sign up to set email alerts
|

Coping with COVID-19: Differences in hope, resilience, and mental well-being across U.S. racial groups

Abstract: Objectives To explore if the COVID-19 pandemic revealed differences across racial groups in coping, resilience, and optimism, all of which have implications for health and mental well-being. Methods We collect data obtained from four rounds of a national sample of 5,000 US survey respondents in each round from April 2020 to February 2021. Using logistic regression and fixed effects models, we estimate the pandemic impacts on COVID-19 related concerns, social distancing behaviors, and mental health/life satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
5
15
0
Order By: Relevance
“…No other mental health score means were found to differ significantly by ethnicity. While this disproves our original hypothesis, it is in line with recent COVID-19 research (Graham et al, 2020;Liu et al, 2020), again explained by some sociologists as a feature of resilience against long-standing oppression, in which low levels of omnipresent stress protect some people against the spikes in stress that the COVID-19 pandemic caused for others (Llera and Newman, 2010;Fishback et al, 2020). This theory is supported by the positive correlation between African-American ethnicity and internal LOC, particularly as it relates to resilience in mental health (Bachem et al, 2020).…”
Section: Demographics and Mental Health Outcomessupporting
confidence: 90%
See 1 more Smart Citation
“…No other mental health score means were found to differ significantly by ethnicity. While this disproves our original hypothesis, it is in line with recent COVID-19 research (Graham et al, 2020;Liu et al, 2020), again explained by some sociologists as a feature of resilience against long-standing oppression, in which low levels of omnipresent stress protect some people against the spikes in stress that the COVID-19 pandemic caused for others (Llera and Newman, 2010;Fishback et al, 2020). This theory is supported by the positive correlation between African-American ethnicity and internal LOC, particularly as it relates to resilience in mental health (Bachem et al, 2020).…”
Section: Demographics and Mental Health Outcomessupporting
confidence: 90%
“…In early 2020, China identified mental health concerns in the general population as well, citing panic, anxiety, and depression as major concerns ( Qiu et al, 2020 ). Actual illness, income and job inequality, governmental preparation and communication, and stigma toward those infected have been cited as concerns for mental health ( Graham et al, 2020 ; Hossain et al, 2021 ; Piltch-Loeb et al, 2021 ). In the United States, of particular concern were loneliness, low distress tolerance, and COVID-19 worry, which are associated with clinical symptoms of depression, anxiety, and post-traumatic stress disorder (PTSD; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their findings suggest that US adults, regardless of racial/ethnic identity, experienced similar levels of psychological distress. Furthermore, Graham et al (2022) noted that Black respondents not only reported better life satisfaction, optimism, and mental health outcomes during the pandemic than their White peers. Although those studies did not examine suicidal ideation as a specific outcome, their findings suggest that factors, such as coping and resilience, may be critical intervention points for improving mental health outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…[24] [25] [26] [27]). Finally, there is a large and growing literature investigating the effects of the pandemic on mental health using data from several countries ([28] [29] [30] [31] [32] [33] [34] [35] [36] [37] [38] [39]).…”
Section: Introductionmentioning
confidence: 99%